Principals' Uses and Interpretations of Student Growth Percentile Data. Issue 1 (January 2016) - Clauser, Amanda L.; Keller, Lisa A.; Mcdermott, Kathryn A.
Increasing numbers of states have incorporated measures of students' academic growth into their data and accountability policies. Measuring growth is a statistically complicated task and complex growth measures can be easy to misinterpret. This paper reports on a survey of 317 Massachusetts principals' understanding of the Student Growth Percentile (SGP), a popular growth model. The survey was designed to produce information about how Massachusetts principals use and interpret the SGP and the extent to which they have misconceptions about what SGPs mean. The survey reveals some common misconceptions, often based on confusion about the differences between the norm-referenced SGP and the state's criterion-referenced assessments. We conclude that there is a risk that principals will make inappropriate decisions based on SGPs. Because of their central role in school improvement, principals need better opportunities to learn about how to use SGP and other growth model data.